Investigating non-image forming photoreception in a mouse model of autosomal dominant optic atrophy - Perganta, G (2013)
Autosomal Dominant Optic Atrophy (ADOA) is a progressive optic neuropathy affecting mainly the retinal ganglion cells (RGCs). It is associated with mutations in the Opa1 gene and is phenotypically characterized by decreased visual acuity, central field deficits and colour vision defects. Experimental work on Opa1 mutant mice (B6; C3-Opa1Q285STOP) has permitted further characterisation of the pathophysiology of the disease. A specific functional visual deficit in the photopic negative response of the electroretinogram has been described in these mice, possibly due to altered dendritic pruning of RGCs. However, non-image-forming (NIF) visual function, which is regulated by a subset of RGCs that express the photopigment melanopsin, has not yet been extensively investigated in Opa1 mutant mice. We were interested in whether RGC dysfunction in Opa1 mutants affects NIF behaviours. We evaluated circadian behaviour, sleep behaviour and melanopsin expression in Opa1 mutant mice (Opa1+/-) and littermate controls (Opa1+/+). Opa1 mutant mice were able to entrain their behaviour rhythm to a normal 12:12 hr light/dark cycle, confining their activity to the dark phase. The suppression of activity by acute light exposure at night (negative masking) was equivalent between genotypes. Circadian phase shift responses to 480 nm or 520 nm light pulses during the subjective night were preserved in Opa1+/- mice relative to wildtype controls. The acute induction of sleep by light exposure at night was also present in Opa1+/- mice and not significantly different to Opa1+/+ animals. Immunohistochemical characterisation of melanopsin cells in flatmount retinae revealed no significant differences in cell numbers betweeen genotypes. Melanopsin (Opn4) transcript levels were also equivalent between Opa1 wildtype and mutant mice. There was also no obvious difference in melanopsin cell stratification patterns. The data overwhelmingly support the preservation of the NIF visual system in Opa1 mutant mice. The findings are consistent with patient studies suggesting increased resistance of melanopsin-expressing RGCs in conditions of mitochondrial optic atrophy. Further work is needed to extend our understanding of the possible neuroprotective mechanism involved which could lead to exciting therapeutic strategies.